新冠肺炎大流行下的中介溝通：媒體科技對日常生活的影響 - Dr. Prabu David; 張皪元博士; Dr. Prabu David; Dr. Leanne Chang (國立陽明交通大學傳播與科技學系, 2021)
In this dialogue, Dr. David shares his views on how technology-mediated communication influences everyday life during the COVID pandemic in three aspects: education, well-being, and information. He describes the benefits of technology in bridging social and psychological distances and in seeking health resources. He believes that technology adds new dimensions to known practices and experiences of interaction, though it also creates concerns about information inequities. Dr. David suggests that more research should attend to how culturally-constructed risks are communicated and how misinformation and disinformation can be better managed and controlled at policy, group, and individual levels in a world with multiple realities. In closing, he emphasizes that we should not mistakenly assume that virtual interactions can replace the essential role of human connection in communication.
Mediated Communication During COVID-19 Pandemic: Influences of Media Technologies in Everyday Life